Chris gets ear tubes - Pace, Betty, 1941-; Hutton, Kathryn (Washington, D.C. : Kendall Green Publications, 1987)
Describes the experience of a young boy whose chronic ear infections are affecting his hearing, until he goes into the hospital for a simple operation.
Keywords: Ear -- Diseases; Hospitals; Medical care; Otitis media in children -- Prevention -- Juvenile literature; Otitis media in children -- Surgery -- Juvenile literature; Otitis media